If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4y + -9) = 5(y + -4) Reorder the terms: 2(-9 + 4y) = 5(y + -4) (-9 * 2 + 4y * 2) = 5(y + -4) (-18 + 8y) = 5(y + -4) Reorder the terms: -18 + 8y = 5(-4 + y) -18 + 8y = (-4 * 5 + y * 5) -18 + 8y = (-20 + 5y) Solving -18 + 8y = -20 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -18 + 8y + -5y = -20 + 5y + -5y Combine like terms: 8y + -5y = 3y -18 + 3y = -20 + 5y + -5y Combine like terms: 5y + -5y = 0 -18 + 3y = -20 + 0 -18 + 3y = -20 Add '18' to each side of the equation. -18 + 18 + 3y = -20 + 18 Combine like terms: -18 + 18 = 0 0 + 3y = -20 + 18 3y = -20 + 18 Combine like terms: -20 + 18 = -2 3y = -2 Divide each side by '3'. y = -0.6666666667 Simplifying y = -0.6666666667
| 2x^4-3x^3+5x^2+5x-7=0 | | 1/(x+9)^2 | | 32/4(8) | | .10x+.25y=7.45 | | 2x+6=7x-2 | | 2(5x+4)=2(3m-10) | | 1/2q-1=6 | | 38-4x=5x+16 | | 7/8x+1/2=7/8 | | 34x+5=10 | | (6x+7/6)+(3/2)=-2x/7 | | -4-2x=12-8x | | x^4-18x^3+81x^2=0 | | 3(x+4)-4(x-3)= | | (6x+7/6)+(3/2)=-2 | | 2q-1=6 | | 4v^2-20v=0 | | 11-8x=139-36x | | 75-4x=14-8x | | x*3a=27 | | ((x-4)+1)/(x+1)=1/2 | | 5x^2+6x-12=2x | | 13b*17= | | 14n-21/7 | | 1/3x+5/6x=7/8 | | 8+(5-4x)-(1-x)=5x-2(x-3) | | 0.7/x=21 | | 7x+12=6+5x | | y=75+20x | | 8(c-2)-(c+3)= | | ((7x-1)/4)-1/3(2x-(1-x)/2)=19/3 | | 18(-x-2)-4(-9+3)=-14 |